On a Class of Poverty Measures - Kakwani, Nanak (Econometrica, 1980)
[This paper provides a generalization of Sen's poverty measure. The generalization is motivated by the failure of Sen's poverty measure to satisfy some transfer-sensitivity axioms proposed in this paper. A numerical method of computing the alternative poverty measures is provided along with an illustration based on the data from the Australian household expenditure survey carried out during 1974.]